ANALYSIS AND SOLUTION OF THE ROMANIAN AGRICULTURAL EDUCATION ISSUES - IOANA ROMAN (Studia Universitatis Babes-Bolyai, 2010)
ABSTRACT. Romanian Agricultural education in the general social context and as against the requirements of the economic development at European- and world level is regarded as an important link in the consolidation and organization of the agricultural industry, as well as the superior valorization of human- and material resources. The activities referring to education in agriculture are meant to signal the necessity to grant an adequate status to this basic economic sector which at this time is suffering image degradation with the tendency to aggravate. In order to identify where to act to solve the problems felt in the system of the agricultural education, the Ishikawa and arbor diagrams have been used. The problems submitted to analysis were: adjustment of agricultural education to the present demands of agriculture; enhance the efficacy of the practical part on the field of agricultural education; human- and material resources of the agricultural school groups and universities; to put into practice the knowledge acquired in the process of agricultural education.